The icat as a natural interaction partner: playing go fish with a robot - Hindriks, Koen; Neerincx, Mark A.; Vink, Mirek (Proceedings of the 10th international conference on Advanced Agent Technology, 2011)
To be able to develop robots that naturally interact with humans it is important to gain a better understanding of the factors that shape this interaction. Although many aspects have already been studied in depth, few studies have been performed on the effect that socio-cognitive abilities may have on this interaction. We have developed a robot that shows intentional or proactive behavior and that can be used to conduct research on interaction that is shaped by cognitive abilities. We have used the iCat robot platform to perform experiments with children to test various hypotheses on perceived effects of socio-cognitive abilities. Two different versions were developed: a socio-cognitive iCat robot that behaves socially and takes the mood of the child into account, and an ego-reactive iCat robot that does not do so. These two robots were evaluated and compared with each other in a scenario where the robot plays the card game Go Fish with a child. Results indicate that children are more positive about the interaction with the socio-cognitive iCat than with the ego-reactive iCat.